Factors Associated With Long-term Risk of Recurrence After Percutaneous Radiofrequency Thermocoagulation of the Gasserian Ganglion for Patients With Trigeminal Neuralgia: A Multicenter Retrospective Analysis. Issue 12 (December 2019) - Zheng, Shuyue; Li, Xiuhua; Li, Ran; Yang, Liqiang; He, Liangliang; Cao, Guoqing; Yang, Zhanmin; Ni, Jiaxiang
Abstract : Objective: This study aimed to estimate risk factors associated with recurrence after radiofrequency thermocoagulation (RFT) of the Gasserian ganglion among a large sample of patients with trigeminal neuralgia (TN) during a long-term follow-up. Materials and Methods: We performed a multicenter retrospective analysis of data from 1481 patients with TN who underwent RFT from 2005 through 2017. Recurrence-free survival (RFS) was assessed by the Kaplan-Meier method. Risk factors of all patient characteristics were determined by using univariate and multivariate Cox regression analysis. Prognostic value was determined by prognostic index (PI) with regression coefficients and receiver-operating characteristic curve model. Results: The median of RFS was 136 months (95% confidence interval [CI]: 123.5-148.5). The rate of RFS was 85.3% (95% CI: 83.5%-87.1%) at 1 year, 74.6% (95% CI: 72.2%-77.0%) at 3 years, 68.0% (95% CI: 65.5%-70.5%) at 5 years, and 54.9% (95% CI: 51.6%-58.2%) at 10 years. Multivariate analysis showed that atypical facial pain (hazard ratio [HR]=16.914, 95% CI: 13.117-21.808, P <0.001), Barrow Neurological Institute (BNI) Class II/III facial hypesthesia before undergoing RFT (HR=2.47, 95% CI: 1.52-4.016, P <0.001)/(HR=3.288, 95% CI: 1.035-10.433, P =0.044), and history of previous microvascular decompression/RFT/neurosurgeries≥2 (HR=1.642, 95% CI: 0.941-2.863, P =0.041)/(HR=2.808, 95% CI: 1.819-4.334, P <0.001)/(HR=3.83, 95% CI: 1.802-8.146, P <0.001) were independently associated with RFS. Patients with PI>0.764 were identified as high-risk patients for TN recurrence with a median RFS of 36 months (95% CI: 23.9-48.1) compared with those with PI<0.764 (HR=6.785, 95% CI: 5.371-8.573, P <0.001). Discussion: Our results indicated the patients with a higher risk for recurrence after RFT for the treatment of TN. In addition, our findings might provide support for clinical decision-making before the RFT procedure.